A finite element strategy to investigate the free expansion behaviour of a biodegradable polymeric stent. Issue 10 (16th July 2015) - Debusschere, Nic; Segers, Patrick; Dubruel, Peter; Verhegghe, Benedict; De Beule, Matthieu
Abstract: Bioresorbable stents represent a promising technological development within the field of cardiovascular angioplasty because of their ability to avoid long-term side effects of conventional stents such as in-stent restenosis, late stent thrombosis and fatigue induced strut fracture. Finite element simulations have proven to present a useful research tool for the design and mechanical analysis of stents. However, biodegradable stents pose new challenges because of their transitional mechanical behaviour. For polymeric biodegradable stents, viscoplastic effects have to be accounted for. This paper presents a method to analyse the mechanical behaviour of polymeric bioresorbable stents using an implicit finite-element solver. As an example, we investigate the mechanical behaviour of a commercially available bioresorbable stent. We examine how, due to the visco-elastic properties of the stent material, the balloon deployment rate influences the mechanical integrity of the stent.